2021
DOI: 10.3390/app11188481
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation Method to Optimize External Fixator Configuration in Long Bone Fractures—Conceptual Model and Experimental Validation Using Pilot Study

Abstract: External fixation is a commonly used method in stabilizing fracture sites. The performance of the fixator depends on how it affects the mechanical properties of the fracture site and is governed by parameters like the fixator type and fixator configuration. Identifying ideal configurations prior to surgery will help surgeons in planning the procedure, limiting the possibility of complications such as non-union. In this study, a framework has been proposed as a surgical pre-planning tool, to assist surgeons com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…There have been many studies on low-cost external fixators, but most of them have reported the clinical outcomes ( 2 , 26 28 ) often without performing thorough biomechanical investigations ( 10 , 19 , 29 ). This could be associated with the circumstances that the devices have been developed under, i.e., poor economical condition or conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies on low-cost external fixators, but most of them have reported the clinical outcomes ( 2 , 26 28 ) often without performing thorough biomechanical investigations ( 10 , 19 , 29 ). This could be associated with the circumstances that the devices have been developed under, i.e., poor economical condition or conflict.…”
Section: Discussionmentioning
confidence: 99%
“…During the project, several versions of the device were developed and modified according to the feedback received from the local partners and surgeons. The final design only is discussed in this paper and other designs were investigated by our partners in Sri Lanka ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Whether this is attributable to the treatment itself, the thin-wire circular device, or the severity of the injury was unclear, a prolonged healing time for tibial fractures treated with external fixators has been reported in the literature, which may lead to an increased risk of loss of wire pre-tension, potentially affecting the process of fracture healing [22,23]. It has been shown that changes in the mechanical properties of a fracture site affect the time taken for a fracture to heal, thus modifying the type and proportion of tissues formed [24]. In addition, poor new bone formation and premature removal can lead to axial deformity and re-fracture of the new bone [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such studies will be able to identify the most cost-effective material and manufacturing technique for each component of the EF, which when incorporated into conceptual models such as the one developed by Sellahewa et al. [129] ,can lead to better optimization and customization of EFs in the future.…”
Section: Analysis Of the Review- Conclusion And Future Directionsmentioning
confidence: 99%